Avaliação da atividade antimicrobiana in vitro e da resposta do complexo dentinopulpar in vivo após capeamento direto com Aloe vera L. em ratos - Alfonso Gala Garcia (2005)
Aloe vera has been extensively studied in search for effective and less toxic antimicrobial and anti-inflammatory agents. The efficacy of in vitro Aloe vera Linné (Aloe vera L.) antimicrobial formulations as juice (G1), gel (G2), and freeze-dried powder (G3) against Streptococcus mutans (UFRJ), Enterococcus faecalis (ATCC14508), Staphylococcus aureus (ATCC 27664), Lactobacillus casei (ATCC 7469), Candida albicans (ATCC 18804) and Actinobacillus actinomycetemcomitans (Y4FDC) was evaluated. G3 showed bacteriostatic and antifungal activity. In vivo pulp capping was performed to reveal the effects of G3 on pulp reaction after capping. Histopathological examination after pulp capping with Aloe vera L. showed a predominant acute-moderate inflammatory infiltrate after 1 to 7 days, which took a normal pattern from days 14 to 30. In addition, Aloe vera L. stimulated reparative dentine and a formation of complete bridge similarly to Ca(OH)2. Strong superficial necrosis was noted exclusively for Ca(OH)2. In conclusion, freeze-dried Aloe vera L. is a potential candidate as a phytotherapeutic agent in some reversible pulp conditions and to stimulate dentin bridge formation.